Intergenerational education mobility in India: nonlinearity and the Great Gatsby Curve - Kishan, P. K. V.; Rajverma, Abhinav (Frontiers in Sociology, 2024)
IntroductionIntergenerational education mobility, which reflects the degree to which an individual’s educational attainment is independent of their parents’ education, is essential for promoting equal opportunities in society. In the context of India, where socio-economic disparities are deeply entrenched, understanding the dynamics of intergenerational mobility is particularly crucial.MethodsThis paper examines various aspects of intergenerational education mobility in India using data from the Indian Human Development Survey (IHDS), a nationally representative multi-topic survey. We analyze intergenerational mobility across different age cohorts and investigate the nonlinearities in the transmission of education. Additionally, we explore the impact of educational inequality, economic growth, and public expenditure on education on mobility outcomes.ResultsOur analysis reveals a high degree of intergenerational persistence in education, although this persistence has decreased over time. Employing quantile regressions, we observe significant nonlinearities in the relationship between fathers’ and sons’ educational outcomes across the educational distribution. In particular, we find a widening mobility gap between historically advantaged subgroups (urban populations, upper castes, Hindus) and disadvantaged groups (rural populations, lower castes, Muslims) at the middle and upper quantiles. Moreover, we confirm the “Higher Inequality leading to Lesser Mobility” nexus, supporting the ‘Great Gatsby Curve’ within the Indian context. Macroeconomic factors, such as economic growth and public expenditure on education, are positively correlated with educational mobility, suggesting that these factors play a critical role in enhancing mobility.DiscussionThese findings highlight the importance of targeted policy interventions to reduce educational disparities and promote greater intergenerational mobility. The widening mobility gaps between socio-economic and demographic groups emphasize the need for more equitable resource distribution and educational reforms. Future research should explore the multifaceted aspects of intergenerational mobility, incorporating longitudinal studies and regional analyses to deepen our understanding of the underlying mechanisms.